Ultra-sensitive urinary lipoarabinomannan (LAM) immunoassay for tuberculosis detection: a performance evaluationResearch in context - Qisheng Jiang; Carolyn Duncan; Harisha Ramachandraiah; Ige A. George; Sumanth Gandra; Marcos Perez; Lorraine Lillis; David S. Boyle; Scott Crick; Morten Ruhwald; Srikanth Singamaneni (EBioMedicine)
Summary: Background: The development of rapid non-sputum tests remains a global priority to accelerate Tuberculosis (TB) diagnosis and treatment initiation. The only WHO-recommended rapid diagnostic test (RDT), the Alere Determine TB Lipoarabinomannan Ag (AlereLAM) has suboptimal sensitivity. A laboratory-based electrochemiluminescence LAM assay (EclLAM) is the current sensitivity benchmark for RDT development and the gold standard for urinary LAM detection. We assessed the diagnostic accuracy of an ultra-sensitive, Plasmonic Fluor-linked Immunosorbent LAM assay (PFLISA-LAM) compared to Sputum Xpert MTB/RIF, sputum culture and urine EclLAM. Methods: We developed and evaluated the assay performance of PFLISA-LAM. Two sub-studies were conducted using banked urine samples: 1. Preclinical study using 337 well-characterised urine samples for cutoff determination and initial evaluation of the performance of PFLISA-LAM compared to sputum Xpert MTB/RIF and culture. 2. A Diagnostic accuracy assessment study using 77 blinded samples to evaluate the performance of PFLISA-LAM compared to EclLAM versus microbiological reference standard (MRS, Xpert positive and/or culture positive). Findings: PFLISA-LAM has a limit of detection (LOD) of 0.84 ± 0.9 pg/mL when detecting purified LAM spiked in urine. In the preclinical study, the optimal assay cutoff was determined to be 1.7 pg/mL. The sensitivities of PFLISA-LAM and sputum Xpert MTB/RIF compared to culture were 51% (95% confidence interval [CI]: 43%–59%) and 62% (95% CI: 53%–70%). The specificities of PFLISA-LAM and Xpert MTB/RIF were 99% (95% CI: 96%–100%) and 100% (95% CI: 100%–100%). Combining PFLISA-LAM and Xpert MTB/RIF test data, an improved sensitivity of 76% (95% CI: 69%–83%) can be achieved. In the diagnostic study, the sensitivities of EclLAM and PFLISA-LAM assays were 42% (95% CI: 27%–59%) and 73% (95% CI: 56%–85%). The specificities of EclLAM and PFLISA-LAM were 95% (95% CI: 85%–99%) and 98% (95% CI: 88%–100%). Interpretation: With better analytical and diagnostic sensitivity compared to EclLAM, PFLISA-LAM can better detect urinary LAM in TB-positive cases. PFLISA-LAM assay also demonstrated the capability to increase the diagnostic value in detecting urinary LAM, complementing molecular tests, achieving improved diagnostic outcome. Funding: We report no external financial support for conducting the study.